Segments of the ancient cultural landscape in the “Hungarian Corner” of Moravia: A valuable pre-industrial heritage - Jaromír Kolejka; Eva Nováková (Hungarian Geographical Bulletin, 2023)
After a brief historical overview, the paper discusses two basic types of natural and cultural heritage in the territory of the “Hungarian corner” of Moravia. For 300 years, this area called a Campus Lucsco in the southeast of today’s republic was disputed territory between the Czech and Hungarian states. Settlement therefore proceeded slowly in waves depending on the political situation. The present international border was established around the year 1333. Numerous documents of the ancient landscape, probably of medieval origin, have been preserved in the current landscape. They are the ground plans of the cores of municipalities, whether they were founded by Czech or Hungarian landlords on one hand, and the remains of ancient land distribution in the form of narrow strips of agricultural land on the other hand. Other areas succumbed to land consolidation during land reforms in the 20th century. While the ground plans of the village cores are only subject to minor changes, the small-scale use of land is still threatened by further merging. The ground plans of the municipalities and land division at the present time (in colour orthophoto maps) were visually compared with the situation documented by the stable cadastre maps from the 1820s–1830s (see Figure 3). Only identical areas in both sources represent urban and rural segments of the pre-industrial landscape, whose roots go back to the dated Medieval Ages. They are documented on selected representative examples well-preserved ground plans of village cores, probably of integrated Hungarian and Czech origin. Similarly, well-preserved examples of the ancient division of agricultural land in flat and dissected terrain both with poly-functional and mono-functional land use are demonstrated. The best-preserved remnants of the ancient pre-industrial landscape are equal in value to protected areas of nature and cultural monuments. Their number and quality these remnants are threatened by economic pressure.